Naturally mutated spike proteins of SARS-CoV-2 variants show differential levels of cell entry - Ozono, Seiya; Zhang, Yanzhao; Ode, Hirotaka; Tan, Toong Seng; Imai, Kazuo; Miyoshi, Kazuyasu; Kishigami, Satoshi; Ueno, Takamasa; Iwatani, Yasumasa; Suzuki, Tadaki; Tokunaga, Kenzo (bioRxiv, 2020)
The causative agent of the coronavirus disease 2019 (COVID-19) pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is steadily mutating during continuous transmission among humans. Such mutations can occur in the spike (S) protein that binds to the angiotensin-converting enzyme-2 (ACE2) receptor and is cleaved by transmembrane protease serine 2 (TMPRSS2). However, whether S mutations affect SARS-CoV-2 infectivity remains unknown. Here, we show that naturally occurring S mutations can reduce or enhance cell entry via ACE2 and TMPRSS2. A SARS-CoV-2 S-pseudotyped lentivirus exhibits substantially lower entry than SARS-CoV S. Among S variants, the D614G mutant shows the highest cell entry, as supported by structural observations. Nevertheless, the D614G mutant remains susceptible to neutralization by antisera against prototypic viruses. Taken together, these data indicate that the D614G mutant is more infectious than the prototype while maintaining neutralization susceptibility. Competing Interest Statement The authors have declared no competing interest. Footnotes * An author's name was corrected, the references were amended, and Abstract and Methods were slightly revised.